Preservation of plant and animal foods: an overview (2012)
"Generally, human food consists of resources of either plant or animal origin, which cannot be kept long after harvest or slaughter and starts deteriorating rapidly. Thus, it becomes imperative to find various ways of extending the shelf life of these materials/resources. The nature and characteristics of the material, like environment of the food and the interactions between the food and its environment, should be well understood. Traditional methods of food preservation include cold storage, fermentation, salting, drying, curing and smoking. However, the features of these traditional methods are largely centred on non-controllable processes that rely solely on 'chance effects'. Modern food preservation techniques include dehydration, refrigeration, freezing, industrial fermentation, freeze drying, irradiation, evaporation, concentration, thermal processing, use of chemical preservatives, high-pressure technology, plant-derived food preservation technology, modified atmosphere packaging, use of bacteriolytic enzymes and a combination of two or more preservative methods (the hurdle concept), which lend themselves to controllable processes and allow for predictable final product quality attributes to be attainable. Traditional and modern food preservation techniques applicable to some of the common food raw materials are discussed in this chapter."